2020
DOI: 10.1186/s12888-020-02515-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with 30-day and 1-year readmission among psychiatric inpatients in Beijing China: a retrospective, medical record-based analysis

Abstract: Background: Psychiatric readmissions negatively impact patients and their families while increasing healthcare costs. This study aimed at investigating factors associated with psychiatric readmissions within 30 days and 1 year of the index admissions and exploring the possibilities of monitoring and improving psychiatric care quality in China. Methods: Data on index admission, subsequent admission(s), clinical and hospital-related factors were extracted in the inpatient medical record database covering 10 seco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
4
14
1
Order By: Relevance
“…It appeared that patients with OCD who were single, who had more severe comorbid depressive symptoms, who used psychotropic medication, and who had a low quality of life were significantly more likely to have intensive treatment 2 years later. Our results on being single and more severe comorbid depression resemble the results concerning other mental disorders (18,19,21). Thus, also in patients with OCD, these variables predict future intensive treatment.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It appeared that patients with OCD who were single, who had more severe comorbid depressive symptoms, who used psychotropic medication, and who had a low quality of life were significantly more likely to have intensive treatment 2 years later. Our results on being single and more severe comorbid depression resemble the results concerning other mental disorders (18,19,21). Thus, also in patients with OCD, these variables predict future intensive treatment.…”
Section: Discussionsupporting
confidence: 81%
“…A systematic review of 58 papers on predictors of readmission in patients with several mental disorders indicates that previous hospitalization, younger age, being unmarried, having lower financial means, not being satisfied with the index treatment, having more hospital days on the index admission, and a negative attitude toward medication were predicting factors for psychiatric readmission (18). In addition, being male, having psychotic symptoms, a longer duration of untreated psychosis, less social satisfaction, disturbed family dynamics, residing in an urban area, and illegal drugs misuse were found predictive of hospitalization in recent prospective cohort studies involving several mental disorders (18)(19)(20)(21)(22). A population study combined several survey and register databases of 2,638 individuals born in 1953, including interviews with their mothers.…”
Section: Introductionmentioning
confidence: 97%
“…The effective treatment of patients with schizophrenia can be difficult with high readmission rates. Previous studies found that 70.5% patients with schizophrenia were readmitted within 10 years, and 25% were readmitted within 4 months of the first hospitalization [4,5] . Readmissions are often disruptive to patients and their families and place a strain on limited healthcare resources.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies have identified several factors associated with psychiatric readmissions, including sociodemographic factors, clinical factors (e.g. diagnosis, severity, symptom profile, medical comorbidities, treatments, inpatient length of stay), and post-discharge factors (e.g., medication adherence, family and social support, use of community healthcare services) [5,6] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation